Influence of Cutting Parameters and Tool Edge Geometries on the Machinability of AISI 52100 Steel in Hard Whirling - SONG, Shuquan; ZHANG, Yu; CHENG, Jiangtao; ZHANG, Hao; GUAN, Xiangyu; ZUO, Dunwen; SHEN, Xiaoqiang (Engineering Transactions, 2023)
The synergistic effect of prepared tool edge and cutting parameters in hard whirling is still unclear, limiting its application in producing large precision ball screws. This paper aims to reveal the effect mechanism of cutting parameters and edge geometries in the whirling process to improve the stability of ball screw quality. A novel cutting force measurement strategy is proposed, and a systematic study of cutting force, surface quality and tool wear is implemented. The results show that small feed (less than 0.15 mm) and high cutting speed (more than 180 m/min) can ensure machining efficiency and improve surface quality. The machining quality can be improved when the edge radius is 10 μm, and the chamfer size is 0.1 mm×20°. The tool with a 30 μm edge radius has a low probability of early failure, but the later wear is severe and timely sharpening is recommended. This study could guide cutting parameters and edge geometry optimization to improve the stability of the quality in hard whirling.